Off-site modular housing systems – Expeditious solutions for student residence - Oscar Eugenio Bellini; Marianna Arcieri; Maria Teresa Gullace (Agathón)
In a competitive university system, student residences represent an essential infrastructure to support not only hospitality needs but also educational and training activities, promoting concepts of independence, and fostering reciprocal relational exchanges and supports. In order to respond immediately to the current shortage of accommodation places, it is possible to use prefabricated modular housing systems. Thanks to the study of literature and case studies, this paper describes the evolution of this construction system, highlighting limits and potentials. It also provides an overview that defines the reasons and opportunities that could suggest its greater use in the university housing sector, at a time when the speed of execution, product quality and respect for costs are increasingly important factors.